Accelerated atherosclerosis caused by serum amyloid A response in lungs of ApoE−/− mice. Issue 3 (27th February 2021) - Christophersen, Daniel Vest; Møller, Peter; Thomsen, Morten Bækgaard; Lykkesfeldt, Jens; Loft, Steffen; Wallin, Håkan; Vogel, Ulla; Jacobsen, Nicklas Raun
Abstract: Airway exposure to eg particulate matter is associated with cardiovascular disease including atherosclerosis. Acute phase genes, especially Serum Amyloid A3 ( Saa3 ), are highly expressed in the lung following pulmonary exposure to particles. We aimed to investigate whether the human acute phase protein SAA (a homolog to mouse SAA3) accelerated atherosclerotic plaque progression in Apolipoprotein E knockout ( ApoE −/− ) mice. Mice were intratracheally (i.t.) instilled with vehicle (phosphate buffered saline) or 2 µg human SAA once a week for 10 weeks. Plaque progression was assessed in the aorta using noninvasive ultrasound imaging of the aorta arch as well as by en face analysis. Additionally, lipid peroxidation, SAA3, and cholesterol were measured in plasma, inflammation was determined in lung, and mRNA levels of the acute phase genes Saa1 and Saa3 were measured in the liver and lung, respectively. Repeated i.t. instillation with SAA caused a significant progression in the atherosclerotic plaques in the aorta (1.5‐fold). Concomitantly, SAA caused a statistically significant increase in neutrophils in bronchoalveolar lavage fluid (625‐fold), in pulmonary Saa3 (196‐fold), in systemic SAA3 (1.8‐fold) and malondialdehyde levels (1.14‐fold), indicating acute phase response (APR), inflammation and oxidative stress. Finally, pulmonary exposure to SAA significantly decreased the plasma levels of very low‐density lipoproteins ‐ low‐density lipoproteins and total cholesterol, possibly due to lipids being sequestered in macrophages or foam cells in the arterial wall. Combined these results indicate the importance of the pulmonary APR and SAA3 for plaque progression.